Enhancement of the efficacy of synthetic and natural anticancer agents through nanocarrier for colon cancer treatment - Kaushik Mukherjee; Pallobi Dutta; Sourav Dey; Tapan Kumar Giri (Elsevier, 2024)
Colon cancer ranks third amongst type of cancer and second in terms of mortality. Various natural and synthetic anticancer agents have been used for the treatment of colon cancer. However, most anticancer agents have poor aqueous solubility and thus low absorptions and bioavailability. Moreover, the chemotherapeutic agents are unable to differentiate between normal and healthy cells and thus kill both types of cells. Nanocarriers have surfaced as a budding anticancer agent delivery system that could enhance the solubility and bioavailability of the anticancer agents and at the same time specifically deliver them to the cancerous cells. In this regard, gold, polymeric, and solid lipid nanoparticles, dendrimers, liposomes, niosomes, and carbon nanotubes have shown promising results as targeted anticancer drug delivery agents with enhanced bioavailability. The objective of this review article is to highlight these nanocarriers and present a detailed overview of how they have enhanced the efficacy of both synthetic and natural anticancer agents.